A IMPLEMENTATION OF JIGSAW LEARNING METHOD IN IMPROVING STUDENTS' SKILLS IN BAND EXTRACURICULAR ACTIIVITIES AT SMPN 34 SURABAYA: 1. The implementation of the Jigsaw learning model in the Band extracurricular at SMPN 34 Surabaya has been proven to improve students' skills. The observation results showed an increase in the average value of students' skills from 54.12 in the pre-cycle, to 71.96 in the first cycle, and 76.94 in the second cycle. This shows that the Jigsaw model is able to provide a positive impact in improving students' music playing skills gradually. 2. PThe implementation of the Jigsaw model is effective in helping students understand the material and improve their skills in playing music. Although there are some students who experience obstacles or decline in skills in certain cycles, overall, the trend of improvement is still visible. - Nurrahmah, Yolanda Oktavia; Sadhana, Senyum (Solah, 2025)
Band extracurricular is a learning activity carried out outside school hours or intracurricular activities to hone students' interests and talents in the field of music. The extracurricular aims to train students who have a desire to be artistic in the world of music. So it is necessary to choose the right learning model, learning method and learning material to support extracurricular activities at SMPN 34 Surabaya.To determine the improvement in skills and the effectiveness of implementing the Jigsaw learning model in improving students' skills in band extracurricular activities at SMPN 34 Surabaya,This study uses a mixed descriptive method of qualitative and quantitative with an approachClassroom Action Research (CAR) or Classroom Action Research. Classroom Action Research (CAR) focuses on efforts to change current conditions to better conditions. This model is in the form of a continuous cycle, consisting of stages of planning, action, observation, and reflection. The results of this study indicate thatThe application of the Jigsaw learning model can be the right solution to improve students' skills in band extracurricular activities.The implementation of the Jigsaw learning model in the Band extracurricular at SMPN 34 Surabaya has been proven to improve students' skills. The observation results showed an increase in the average value of students' skills from 54.12 in the pre-cycle, to 71.96 in the first cycle, and 76.94 in the second cycle. This shows that the Jigsaw model is able to provide a positive impact in improving students' music playing skills gradually through effective collaboration.